Coastal resources mapping of Besut (Terengganu Coast) using microBRIAN digital mapping technology and Landsat MSS satellite data - Mohammed, Mohd. Ibrahim; Hussein, Nor Azman; Ibrahim, Md. Isa; Kuchler, Debbie A. (1991)
The use of remotely sensed imagery to map the inventory of coastal resources is now a proven technology for Improving the cost efficiency of such mapping practices. Modules contained within the microBRIAN digital image analysis system provide several approaches to achieve the objective of resource mapping. The Faculty of Fisheries and Marine Sciences, Universiti Pertanian Malaysia has employed the combined technology of microBRIAN image processing and Landsat MSS satellite data to produce a coastal resources inventory map of the Besut area. The method utilized the digitizing and classification modules within the microBRIAN system. The steps in the mapping process and the classification result are presented in this paper.